Closed-loop control for performance tuning - PESSOLANO FRANCESCO,MEIJER RINZE I. M. P.,PINEDA DE GYVEZ JOSE D. J (2007)
The present invention relates to a method and circuit arrangement for controlling performance of an integrated circuit in response to a monitored performance indicator, wherein power supply of the integrated circuit is controlled based on said performance indicator. At least one of a noise level of the controlled power supply and a clock frequency generated in said integrated circuit is monitored and a respective control signal is fed back to the controlling function if the checking result is not within a predetermined range. Thereby, an simple and easily extendable automatic adaptation to process variations can be achieved.